2020
DOI: 10.3390/plants9040550
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Regulates Doxorubicin-Induced Liver Dysfunction: Impact on Oxidative Stress and Inflammation

Abstract: Doxorubicin (Dox) is an operational and largely used anticancer drug, used to treat an array of malignancies. Nonetheless, its beneficial use is constrained due to its renal and hepatotoxicity dose dependently. Numerous research findings favor the use of antioxidants may impact Dox-induced liver injury/damage. In the current study, Wistar rats were given naringenin (50 and 100 mg/kg b.wt.) orally for 20 days as prophylactic dose, against the hepatotoxicity induced by single intraperitoneal injection of Dox (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 64 publications
6
40
0
Order By: Relevance
“…For instance, the administration of flavonoid-rich extract of orange juice diminished iNOS in the colon of dinitrobenzene sulfonic acid-treated mice (Fusco et al, 2017). Wali, Rashid, et al (2020) reported that naringenin, at the doses of 50 and 100 mg/kg, decreased the expressions of COX-2 in experimental hepatic inflammation triggered by doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the administration of flavonoid-rich extract of orange juice diminished iNOS in the colon of dinitrobenzene sulfonic acid-treated mice (Fusco et al, 2017). Wali, Rashid, et al (2020) reported that naringenin, at the doses of 50 and 100 mg/kg, decreased the expressions of COX-2 in experimental hepatic inflammation triggered by doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of NF-κB and COX-2 expressions could block the activation of downstream cytokines, and thus, afford protection against propanil-induced hepatotoxicity (Wali, Rashid, et al, 2020).…”
mentioning
confidence: 99%
“…In alleviation of DOX toxicity, phytochemicals reduce levels of proinflammatory cytokines via downregulating NF-κB signaling pathway [ 97 ]. Furthermore, apoptotic proteins such as Bax and caspase-3 undergo downregulation, while antiapoptotic factor Bcl-2 demonstrates an increase in expression to ameliorate DOX side effects [ 98 ].…”
Section: Doxorubicin: Cancer Resistance and Side Effectsmentioning
confidence: 99%
“…Naringenin was found to decrease lipid peroxidation by diminishing membrane fluidity and lowering the production of ROS, increase anti-oxidant enzymes, and decrease the levels of inflammatory mediators. A further histological investigation on liver tissues confirmed the preventative effect of naringenin against doxorubicin-induced hepatotoxicity [ 4 ].…”
Section: Using Various Methodologies To Discover New Plant-derivedmentioning
confidence: 94%